HUMAN RIGHTS EDUCATION AS A PILLAR FOR AN EQUITABLE AND JUST SOCIETY - Silvia Elena Sánchez Acevedo (DIALÉCTICA, 2025)
The article analyzes human rights education, highlighting that, beyond a legal obligation, it is an essential necessity for building just, equitable, and respectful societies. In this context, the importance of an education that not only informs about fundamental rights but also promotes a culture of peace, inclusion, and solidarity is highlighted. Emphasis is placed on the consolidation of public policies by the Ministry of National Education aimed at developing well-rounded citizens with the ability to protect their rights and recognize and value the rights of others. Furthermore, the need for pedagogical strategies that allow students to embrace human rights as part of their identity and daily practice is emphasized. The text examines the role of educational institutions as key spaces for promoting these rights, highlighting collaboration between teachers, students, families, and the community. It also incorporates the reflections of Paulo Freire and Abraham Magendzo on the urgency of critical, participatory, and transformative education, capable of empowering communities and generating structural change. It particularly highlights the importance of these policies in territories affected by the Colombian armed conflict, where human rights education can contribute to rebuilding the social fabric and promoting peace. By fostering respect and equity, it paves the way for reconciliation and community strengthening. In conclusion, human rights education is proposed as an essential means to promote profound social change and foster coexistence based on equity, respect, and a democratic culture.